Occupational health hazards and morbidity among nurserymen in a rural area of West Bengal - Ratul Kumar Bysack; Sreetama Chakrabarti; Somnath Naskar; Soma Chakrabarti; Mausumi Basu (Wolters Kluwer Medknow Publications, 2023)
Background: Horticulture or working in plant nursery is one of the main occupations in few areas of the southern part of West Bengal. It is considered as a hazardous health sector worldwide as it possesses several physical, chemical, and biological risks. Objectives: The present study aimed to estimate the occupational health hazards and morbidity profile among the nurserymen living in a rural area of West Bengal and to determine the factors associated with occupational health hazards and morbidity of the participants. Materials and Methods: An observational descriptive, cross-sectional study was conducted from September 2021 to November 2021among 132 nurserymen in a subcenter of South 24 Parganas district of West Bengal through interview using a predesigned, pretested, and structured schedule. Data were analyzed using the SPSS version 25.0. Bivariate and multivariate logistic regression was used to determine the factors associated with health hazards and morbidity. Results: Different types of occupational hazards experienced by the participants were physical (100%), biological (91.6%), ergonomical (91%), chemical (85.6%), and psychological (31.8%). Most common occupation-related morbidity reported was skin rash (82.6%) followed by headache (78%), neck pain (78%), and low back pain (59.8%). Multivariate logistic regression revealed that age ≥60 years, daily working hours of ≥7 h and presence of chronic disease were statistically significant covariates of hazards. Female gender and working span of >10 years were significant covariates of "high morbidity" (P < 0.05). Conclusion: One or more types of occupational hazards were experienced by the respondents. Future interventions to address hazards and morbidities of the workers along with the development of preventive measures are the need of the hour.